The Anti-Manichaean Treatise De fide contra Manichaeos, Attributed to Evodius of Uzalis Critical Edition and Translation - Vanspauwen, Aäron 1990-; Evodius Uzalitanus -424 (2018)
This contribution offers a new critical edition of the treatise De fide contra Manichaeos, a Latin anti-Manichaean tractate attributed to Evodius of Uzalis. The edition is the result of the study of all extant manuscripts of De fide, 30 in total. The introduction offers a thorough discussion of the textual transmission of De fide, in which I attempt to assess the relations between all manuscripts. De fide has been transmitted in three major branches, with one manuscript not pertaining to one particular branch of the transmission. The archetype of De fide appears to have contained a collection of seven African anti-heretical texts. In the introduction I also discuss previous editions of De fide, including the edition of the Maurists and the most recent edition of Zycha in the CSEL series. The main section of the contribution consists of the new critical edition, with three apparatuses: a biblical apparatus, an apparatus of Manichaean and apocryphal source texts, and a (negative) critical apparatus. The critical apparatus contains the textual variants of all manuscripts with the exception of the codices descripti. A facing translation in English, with additional footnotes, complements the Latin text. In a final section, I discuss several textual-critical choices in greater detail.
Enthält die Edition von "De fide contra Manichaeos" in lateinischer Sprache und englischer Übersetzung Seite 44-105